2018
DOI: 10.1002/hep.29804
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids stimulate cholangiocyte fluid secretion by activation of transmembrane member 16A Cl− channels

Abstract: Bile acids stimulate a bicarbonate‐rich choleresis, in part, through effects on cholangiocytes. Because Cl− channels in the apical membrane of cholangiocytes provide the driving force for secretion and transmembrane member 16A (TMEM16A) has been identified as the Ca2+‐activated Cl− channel in the apical membrane of cholangiocytes, the aim of the present study was to determine whether TMEM16A is the target of bile‐acid–stimulated Cl− secretion and to identify the regulatory pathway involved. In these studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 34 publications
0
55
0
1
Order By: Relevance
“…First, ITPR3 plays an important role in regulating bicarbonate secretion in cholangiocytes. It is most concentrated in a specialized region of the endoplasmic reticulum (ER) beneath the apical membrane, where it is positioned to release calcium to activate the calcium‐dependent chloride channel, transmembrane member 16a, which, in turn, couples with the chloride‐bicarbonate exchanger, anion exchanger 2, to result in net bicarbonate secretion . This ITPR3 pool is effectively released by nucleotides in bile, which activate apical P2Y receptors, resulting in local formation of InsP3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, ITPR3 plays an important role in regulating bicarbonate secretion in cholangiocytes. It is most concentrated in a specialized region of the endoplasmic reticulum (ER) beneath the apical membrane, where it is positioned to release calcium to activate the calcium‐dependent chloride channel, transmembrane member 16a, which, in turn, couples with the chloride‐bicarbonate exchanger, anion exchanger 2, to result in net bicarbonate secretion . This ITPR3 pool is effectively released by nucleotides in bile, which activate apical P2Y receptors, resulting in local formation of InsP3 .…”
Section: Discussionmentioning
confidence: 99%
“…It is most concentrated in a specialized region of the endoplasmic reticulum (ER) beneath the apical membrane, where it is positioned to release calcium to activate the calcium-dependent chloride channel, transmembrane member 16a, which, in turn, couples with the chloride-bicarbonate exchanger, anion exchanger 2, to result in net bicarbonate secretion. (25) This ITPR3 pool is effectively released by nucleotides in bile, which activate apical P2Y receptors, resulting in local formation of InsP3. (13) Although hepatocytes can secrete ATP into bile, (26,27) activation of the cystic fibrosis transmembrane conductance regulator in FIg.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TUDCA was demonstrated to augment the secretory capacity of hepatocytes and cholangiocytes by stimulation of vesicular exocytosis through Ca 2+ -/cPKCα-dependent vesicle fusion process and insertion of key transport proteins into their target membrane [66,70]. Later research revealed that TUDCA exerts its choleretic activity via a dual p38 MAPK /integrin-dependent mechanism of apical carrier insertion [73,76] and stimulation of Cl − secretion in cholangiocytes through the activation of membrane Ca 2+ -activated Cl − channel (TMEM16A) [77]. In contrast, TUDCA exerts its anti-cholestatic properties mainly by enhancing secretory capacity of hepatocytes [78].…”
Section: Tudca As Bile Acid In Hepatobiliary Disordersmentioning
confidence: 99%
“…While the majority of this section has been focused on respiratory and colonic epithelium, it is worth noting that TMEM16A has been characterized as the CaCC in several other epithelial tissues [ 73 , 74 , 75 ]. Cell lines of pancreatic ductal cells have been observed to express TMEM16A [ 73 , 75 ].…”
Section: Tmem16a In Epithelial Tissuesmentioning
confidence: 99%